Operating principle of the electromagnetic eight-pole vibrating machine with angular vibrations of armature - Gela Javakhishvili (Theoretical Hypotheses and Empirical Results, 2025)
This paper describes operating principle of the electromagnetic eight-pole viaaing machine with angular vibrations of armature. The vibrating machine comprises a asymmetrical eight-pole armature with a DC winding and eight-pole symmetrical stator with an AC winding with four parallel branches. The amplitude of oscillations of the working element is regulated depending on the distance of the attachment on the lever and the current in the DC winding. This vibrating machine is designed for the use in industry as a drive for feeders, transporters, sorters and for a number of other purposes where a vibratory drive with directional oscillations is needed. The novelty of the design is protected by patent of Georgia